If n is a positive integer, which of following statement is individually sufficient to prove whether 289 is a factor of n?a. The greatest common divisor of n and 344 is 86. b. Least common multiple of n and 272 is 4624. c. The least common multiple of n and 289 is 289n.

Answers

Answer 1
Answer:

Answer:

The statement b) is individually sufficient to prove than 289 is a factor of n

Step-by-step explanation:

The least common multiple of n and 272 is the smallest number that is a multiple of n and a multiple of 272. Therefore:

272 x X = 4624 ⇒ X = 17 but 272 = 17 · 16 and 289 = 17 · 17

Therefore 17·17 must be a factor of n. That means 289 is a factor of n


Related Questions

Determine the x-intercept of the line whose equation is given:y = StartFraction x Over 2 EndFraction minus 3a.(6, 0)b.(negative 6, 0)c.(0, three-halves)d.(Negative three-halves, 0)
Find the product of 2 5/6 and 3
Find the slope of the line that contains the points:(-6, 3) and (-4, 5).
Which equation represents the polar form of x2 + (y + 4)2 = 16?
Square root of -61 to the nearest tenth

WNu
Apply
6. Nadia is comparing costs for two brands of garden compost. For
Brand A, the cost y for x bags is shown in the table For Brand B,
the cost y can be represented by the equation y = 1,99%, where
x represents the number of bags, Which brand costs less for
6 bags of compost? How much less?

Answers

Brand B costs less for 6 packs of compost. It costs $5.99 less.

Which brand costs less for 6 bags of compost?

To discover which brand costs less for 6 sacks of compost, let's calculate the fetched of 6 packs of each brand:

Brand A:

6 sacks * $2.99/bag = $17.94

Brand B:

y = 1.99x

For 6 packs of compost, x = 6:

y = 1.99 * 6 = $11.94

In this manner, Brand B costs less for 6 sacks of compost, and it costs $5.99 less.

Brand B costs less for 6 packs of compost. It costs $5.99 less.

Learn more about compost here:

brainly.com/question/15334467

#SPJ3

Find the value of this expression if x = 9. x^2+7/x+2​

Answers

Answer:

8

Step-by-step explanation:

Answer:

Yeah, the answer is 8.

Step-by-step explanation:

I've gotten this question and it's right.

Raghav has to load 2456 cartons of apples equally in 5 trucks. how many cartons will be left unloaded in the end?​

Answers

Answer:

12,280

Step-by-step explanation:

just do 1456×5 :))

6. The length of the minor arc AB of a circle, centre O, is 2π cm and the length of the major arc is 22π cm. Find: a) the radius of the circle
b) the acute angle AOB. ​

Answers

Answer:

a) 24 [cm]; b) 30°.

Step-by-step explanation:

a) the length of full the circle is: min_arc(AB)+maj_arc(AB)=π(22+2)=24π [cm]. Then the radius is: r=L/π; ⇒ r=24π/π=24 [cm];

b) if the full circle is 360° (L=24π), then m(∠AOB):2=360°:24 and the required measure of the acute angle AOB is:

m(∠AOB)=360*(1/12)=30°.

Write a simplified expression for the area of the rectangle below

Answers

Answer:

= 12x + 40

Step-by-step explanation:

area = l * b \n  = 20 *  ((3)/(5) x + 2)  \n  =  (60x)/(5)  + 40 \n  = 12x + 40

hope this helps

brainliest appreciated

good luck! have a nice day!

Select all the correct answers.Which expressions are equivalent to the given expression.
y^-8y^3x^0x^-2​

Answers

Answer:

x^(-2)y^(-5)

Step-by-step explanation:

The options are not given; however, the question can still be solved

Given

y^(-8)y^3x^0x^-2

Required

Simplify

Start by rewriting the expression

y^(-8) * y^3 * x^0 * x^(-2)

Apply the following laws of indices: a^x * a^y = a^(x+y)

This gives:

y^(-8+3) * x^(0-2)

Evaluate the exponents

y^(-5) * x^(-2)

x^(-2)y^(-5)

Hence, x^(-2)y^(-5) is equivalent to y^(-8)y^3x^0x^-2

The expression which is equivalent to the exponential equation is x^(-2)y^(-5).

Given data:

The exponential form is an easier way of writing repeated multiplication involving base and exponents. It has a base and a power

The exponential form of a number is a way of representing a number using exponents, where the base is typically a number greater than 1.

The exponential expression is represented as y^(-8)y^(3)x^(0)x^(-2).

From the laws of exponents:

m^(a)*m^(b)= m^(a+b)

(m^(a))/(m^(b))= m^(a-b)

So, the expression is simplified as:

y^(-8)y^(3)x^(0)x^(-2)=x^(-2)y^(-5)

Hence, the equivalent expression is x^(-2)y^(-5).

To learn more about exponents, refer:

brainly.com/question/28966438

#SPJ3